2018
DOI: 10.3988/jcn.2018.14.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Ischemic Stroke during Sleep in Apneic Patients

Abstract: Background and PurposeThe literature indicates that obstructive sleep apnea (OSA) increases the risk of ischemic stroke. However, the causal relationship between OSA and ischemic stroke is not well established. This study examined whether preexisting OSA symptoms affect the onset of acute ischemic stroke.MethodsWe investigated consecutive patients who were admitted with acute ischemic stroke, using a standardized protocol including the Berlin Questionnaire on symptoms of OSA prior to stroke. The collected stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
(31 reference statements)
0
6
0
1
Order By: Relevance
“…This topic was researched by Barreto et al, Haula et al, and Schütz et al [ 32 , 33 , 34 ] and the results of cited studies suggested that preexisting sleep apnea is associated with the occurrence of WUS or even with worse short-term outcomes measured in mRS [ 33 ]. Kim et al in 2018, using the Berlin Questionnaire [ 10 ], found that preexisting witnessed or self-recognized sleep apnea was significantly more frequent in WUS when compared to the non-WUS population (28.3% vs. 16.6%, p = 0.036). In the same study, the presence of preexisting witnessed or self-recognized sleep apnea was the only risk factor for WUS (adjusted odds ratio = 2.055, 95% confidence interval = 1.035–4.083, p = 0.040) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This topic was researched by Barreto et al, Haula et al, and Schütz et al [ 32 , 33 , 34 ] and the results of cited studies suggested that preexisting sleep apnea is associated with the occurrence of WUS or even with worse short-term outcomes measured in mRS [ 33 ]. Kim et al in 2018, using the Berlin Questionnaire [ 10 ], found that preexisting witnessed or self-recognized sleep apnea was significantly more frequent in WUS when compared to the non-WUS population (28.3% vs. 16.6%, p = 0.036). In the same study, the presence of preexisting witnessed or self-recognized sleep apnea was the only risk factor for WUS (adjusted odds ratio = 2.055, 95% confidence interval = 1.035–4.083, p = 0.040) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 13 studies’ results showed that sleep apnea syndrome (SAS) is significantly higher in WUS patients, with significantly higher apnea-hypopnea index (AHI; 95% confidence interval: 1.38–14.11; p = 0.017) and oxygen desaturation index (ODI; 95% confidence interval: 0.261–7.438; p = 0.035) [ 8 ]. Increased risk of stroke in these patients may be mediated by hemodynamic changes due to sleep apnea, oxidative stress, endothelial dysfunction, sympathetic overactivity, metabolic dysregulation, accelerated hypertension, paradoxical embolism, or arrhythmogenesis [ 9 , 10 ]. Polysomnography (PSG) is a gold standard diagnostic tool for the complex estimation of SDB.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is characterized by high morbidity, mortality and disability rates, with World Health Organization (WHO) surveys showing that 15 million new stroke cases occur per year worldwide (1)(2)(3). Effective protection against ischemic brain damage is a worldwide conundrum, necessitating research into novel approaches for control of ischemiareperfusion (I/R) injury.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, a SAOS pode contribuir para o acidente vascular cerebral (AVC) isquêmico, não apenas como um fator predisponente, mas também como um fator desencadeante. O tratamento da SAOS pode, portanto, ser benéfico na prevenção do AVC, particularmente no que ocorre durante o sono 10 .…”
Section: Introductionunclassified